2003
DOI: 10.1046/j.1469-8986.2003.00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of sleepiness when driving

Abstract: The extent to which sleepy drivers are aware of sleepiness has implications for the prevention of sleep-related crashes, especially for drivers younger than 30 years old who are most at risk. Using a real car interactive simulator, we report on EEG, subjective sleepiness, and lane drifting (sleepiness-related driving impairment) from 38 sleep-restricted, healthy young adults undergoing nontreatment control conditions from three (unpublished) investigations using the same experimental protocols for assessing va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
96
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(105 citation statements)
references
References 13 publications
7
96
1
1
Order By: Relevance
“…This level of self-awareness of increasing sleepiness when driving is similar to what we have found with a group of healthy drivers of a similar age (mean age 66.6y [52-74y]) having undergone sleep restriction [11], and in young male adult drivers [19,20].…”
Section: Discussionsupporting
confidence: 87%
“…This level of self-awareness of increasing sleepiness when driving is similar to what we have found with a group of healthy drivers of a similar age (mean age 66.6y [52-74y]) having undergone sleep restriction [11], and in young male adult drivers [19,20].…”
Section: Discussionsupporting
confidence: 87%
“…We found that postnight-shift drivers were much sleepier, and noticed increasing difficulty keeping their eyes open and maintaining lane position, particularly when driving for more than 15-30 min, which has been related to slowing on EEG (increased θ power), lane drifting and severe driving impairment during simulated driving, and increased crash risk (2,(31)(32)(33). Our findings on the controlled driving track were comparable to a study of nurses driving home after night shift, which showed that the maximum total blink duration was increased after the night shift and was associated with a greater incidence of subjective sleep-related events, such as "resting your eyes," or "falling asleep at the stop light" (21).…”
Section: Discussionmentioning
confidence: 95%
“…While subjective assessments of sleepiness have been found to be accurate in the laboratory, their relationship to objective sleepiness measures has not been shown reliably in applied settings. 43,44 Hence, selfratings of sleepiness have limited value in the workplace compared to objective sleepiness measures, which do not rely upon the accuracy of an individual's introspection. In-vehicle sleepiness-detection systems provide the driver with immediate notification of their current alertness state and risk of performance impairment and attentional failure in the future, potentially preventing sleepiness-related motor vehicle crashes.…”
Section: Discussionmentioning
confidence: 99%